Enhancing Mentor Teacher Practices through Jelita-Lestari: Developing an Online Journal System for Reflective Collaboration in Teacher Education - Ibrohim, Ibrohim; Muksar, Makbul; Yulianti, Erni; Hajar, Maya Umi (Prosiding Seminar Nasional Pengabdian kepada Masyarakat (SINAPMAS), 2024)
The quality of mentoring mentor teachers provide during the teaching practicum of pre-service teacher education programs significantly impacts the pedagogical competence of prospective teachers. The current study addresses the challenge of enhancing the quality of mentoring provided by mentor teachers in the teaching practicum of the Teacher Professional Education program in the Science Education Study Program at the State University of Malang. The research focuses on developing and implementing